Comparison of visual outcomes after non‐toric and toric implantable collamer lens V4c for myopia and astigmatism. Issue 5 (20th October 2020) - Wei, Ruoyan; Li, Meiyan; Niu, Lingling; Aruma, Aruma; Miao, Huamao; Shen, Yang; Yao, Peijun; Wang, Xiaoying; Zhang, Huihui; Zhou, Xingtao
Abstract: Purpose: To evaluate the visual quality of myopic patients after non‐toric versus toric implantable collamer lens (ICL and TICL, respectively) V4c, and to investigate the potential risk factors of postoperative night vision disturbances. Methods: This prospective cohort study included 42 eyes of 21 patients treated with ICL and 46 eyes of 23 patients treated with TICL. Refractive parameters and ocular aberrations were examined before and 6 months after surgery. Subjective quality of vision was scored by a validated questionnaire. Results: The efficacy index at 6 months was 1.14 ± 0.20 for ICL and 1.17 ± 0.16 for TICL; the safety index was 1.20 ± 0.17 for ICL and 1.20 ± 0.19 for TICL. The root mean square of total higher‐order aberrations (HOAs) and trefoil was significantly increased, and no statistical differences between groups were detected in HOA changes. Many patients reported haloes (85.7% for ICL and 100% for TICL) and glare (76.2% for ICL and 65.2% for TICL), but most (94.4% for ICL and 95.5% for TICL) were satisfied or very satisfied with visual outcomes. Implantable collamer lens (ICL) toricity was the risk factor for frequency (OR = 2.81, p = 0.01), severity (OR = 3.85, p = 0.003) and bothering effect (OR = 2.89, p = 0.01) of haloes. Conclusions: Implantable collamer lens and TICL provided comparable efficacy, safety and predictability, induced acceptable level of HOAs and achieved high satisfaction in correcting myopia and myopic astigmatism. Although not severe, haloes and glare have a non‐negligible prevalence and ICL toricity is a potential risk factor of haloes.